2017
DOI: 10.1002/2016gl072446
|View full text |Cite
|
Sign up to set email alerts
|

New properties of whistler modes

Abstract: Two new properties of whistler modes have been observed in a large laboratory plasma which are relevant to whistler waves in space plasmas. The first is the reflection of whistler modes by nonuniform magnetic fields whose gradient scale length is comparable to the wavelength. Such situations may arise near shock waves, reconnection geometries, lunar crustal magnetic fields, and possibly for long wavelength whistlers in dipolar fields. The second observation shows that whistler modes can have linear polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This indicates that the transverse propagation direction of the reflected whistler waves may depend on their initial wave properties, such as wave frequency and wave normal angle (Bortnik et al, 2008; Bortnik et al, 2011; He et al, 2015). It should also be mentioned that a strong standing wave pattern and linear polarization in the LHR reflection region, which are shown in our simulation results in sections 3.1 and 3.2, are similar to the observation in a laboratory plasma experiment on the new reflection mechanism of whistler mode waves by Stenzel and Urrutia (2017). The signatures from simulated magnetospheric reflection can be compared with observation evidence from satellites near the LHR reflection region in the magnetosphere, which is left as a future study.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…This indicates that the transverse propagation direction of the reflected whistler waves may depend on their initial wave properties, such as wave frequency and wave normal angle (Bortnik et al, 2008; Bortnik et al, 2011; He et al, 2015). It should also be mentioned that a strong standing wave pattern and linear polarization in the LHR reflection region, which are shown in our simulation results in sections 3.1 and 3.2, are similar to the observation in a laboratory plasma experiment on the new reflection mechanism of whistler mode waves by Stenzel and Urrutia (2017). The signatures from simulated magnetospheric reflection can be compared with observation evidence from satellites near the LHR reflection region in the magnetosphere, which is left as a future study.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…This effect has been shown and explained in a recent letter. 48 In the present work, we observe in detail the motion of the incident phase front in an ambient magnetic field whose curvature changes on a scale smaller than a wavelength. The off-axial field lines bend faster than the phase front such that the incident wave changes from oblique to perpendicular and beyond.…”
Section: Wave Reflection Mechanism In Highly Nonuniform Magnetic Fmentioning
confidence: 81%
“…It is thus suggested that a majority of whistler mode waves in the Martian magnetosphere are almost linearly polarized and propagating obliquely with respect to the background magnetic field. Linear polarization may be due to the interference of the circular polarized waves while propagating in opposite directions, and oblique propagating waves may be caused by wave refraction during propagation away from source regions (Chen et al., 2013; Stenzel & Urrutia, 2017; Yu & Yuan, 2022). However, the reason why linearly polarized and oblique propagating waves dominate is not yet conclusive, which will be further explored in the future work.…”
Section: Statistical Resultsmentioning
confidence: 99%